2017
DOI: 10.1097/aap.0000000000000650
|View full text |Cite
|
Sign up to set email alerts
|

Focused Cardiac Ultrasound for the Regional Anesthesiologist and Pain Specialist

Abstract: This article in our point-of-care ultrasound (PoCUS) series discusses the benefits of focused cardiac ultrasound (FoCUS) for the regional anesthesiologist and pain specialist. Focused cardiac US is an important tool for all anesthesiologists assessing patients with critical conditions such as shock and cardiac arrest. However, given that ultrasound-guided regional anesthesia is emerging as the new standard of care, there is an expanding role for ultrasound in the perioperative setting for regional anesthesiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Given a recent call to action for a formal perioperative ultrasound training for anesthesiology residencies [ 15 ], in addition to a push to embrace focused cardiac ultrasound within anesthesia subspecialties [ 16 ] as well as the profession in general [ 17 ], it is clear that formal training in this skill will need to be embraced by anesthesia training programs in the not to distant future. As the anesthesiologist’s role continues to evolve around peri-operative management and care, the use of point-of-care and goal-directed ultrasonography should be incorporated into daily practice to help guide fast and accurate diagnoses of potentially life-threatening conditions in time-limited situations.…”
Section: Discussionmentioning
confidence: 99%
“…Given a recent call to action for a formal perioperative ultrasound training for anesthesiology residencies [ 15 ], in addition to a push to embrace focused cardiac ultrasound within anesthesia subspecialties [ 16 ] as well as the profession in general [ 17 ], it is clear that formal training in this skill will need to be embraced by anesthesia training programs in the not to distant future. As the anesthesiologist’s role continues to evolve around peri-operative management and care, the use of point-of-care and goal-directed ultrasonography should be incorporated into daily practice to help guide fast and accurate diagnoses of potentially life-threatening conditions in time-limited situations.…”
Section: Discussionmentioning
confidence: 99%
“…2, 3 We appreciate their knowledge and perspective as cardiologists and agree that there are certain limitations associated with FoCUS. Although we do acknowledge these limitations in our article, our goal of this series is to encourage regional anesthesiologists proficient in ultrasound-guided regional anesthesia to add this to their clinical toolbox by learning these exceedingly relevant PoCUS skills.…”
Section: Reply To Drs Saranteas and Panoumentioning
confidence: 98%
“…Focused cardiac ultrasound can answer simple, yet potentially lifesaving "yes or no" clinical questions, such as whether there is the presence of severe aortic stenosis, significant hypovolemia, a significant cardiomyopathy, or a massive pulmonary embolism. 3 Although FoCUS is not a continuous monitoring device such as an arterial line or pulmonary arterial catheter, the benefits of FoCUS come from it being a noninvasive technology that can be performed repeatedly, reliably, and rapidly at the bedside in any location within the perioperative setting. Several studies have demonstrated that this skill is rapid and effective in the hands of a skilled clinician, with 1 study showing that image interpretation with a pocket-sized ultrasound machine can be successfully performed in approximately 10 seconds for any basic FoCUS view, and it takes approximately 60 seconds to obtain all FoCUS views in addition to visualization of the pleura.…”
Section: Reply To Drs Saranteas and Panoumentioning
confidence: 99%
“…2,3 The goal of this series is to encourage regional anesthesiologist proficient in ultrasound-guided regional anesthesia (UGRA) to add to their clinical toolbox by learning these exceedingly relevant PoCUS skills. We agree with Dr Hardman and his colleagues that when it comes to terminology such as "standard of care" there is the medicolegal definition and that we should use cautiously in medical literature until a legal consensus is met.…”
mentioning
confidence: 99%